Studies on the Hydrometallurgical Transfer of Lead, Copper, and Iron from Direct-to-Blister Copper Flash Smelting Slag to Solution Using L-Ascorbic Acid - Krzysztof Gargul; Arkadiusz Pawlik; Michał Stępień (Molecules)
This study explored the behavior of lead, copper, and iron during the leaching process of flash smelting slag from direct-to-blister copper flash smelting using l-ascorbic acid solutions. Flash smelting slag is generated in considerable quantities by various copper smelters worldwide. One drawback of the single-stage flash smelting technology for copper concentrates is the production of large quantities of metal-rich by-products. However, through appropriate management of postprocess waste, valuable components such as copper or lead can be recovered. In practice, the slag is typically subjected to decoppering processes involving electric and converter furnaces. The hydrometallurgical process proposed in this study is aimed at replacing high-temperature recovery methods. The primary objective of the experiments was to investigate the effects of variations in specific leaching parameters and the addition of auxiliary substances on the leaching efficiency of lead, copper, and iron. Four parameters were adjusted during the tests: concentration of l-ascorbic acid, liquid-to-solid phase ratio, temperature, and time. An oxidizing agent in the form of perhydrol and citric acid with an oxidant were used as additives. Optimal process conditions were determined to achieve maximum lead leaching efficiency while maintaining relatively low leaching of copper and iron. The experiments indicated that leaching in ascorbic acid solutions resulted in lead extraction efficiencies ranging from approximately 68% to more than 88%, depending on the conditions. Conversely, relatively low leaching efficiencies of iron (4–12%) and copper (0–29%) were observed.